2003
DOI: 10.1016/s0042-6822(03)00144-2
|View full text |Cite
|
Sign up to set email alerts
|

Curing of foot-and-mouth disease virus from persistently infected cells by ribavirin involves enhanced mutagenesis

Abstract: BHK-21 cells persistently infected with foot-and-mouth disease virus (FMDV) can be cured of virus by treatment with the antiviral nucleoside analogue ribavirin. To study whether the process involved an increase in the number of mutations in the mutant spectrum of the viral population, viral genomes were cloned from persistently infected cells treated or untreated with ribavirin. An increase of up to 10-fold in mutation frequencies associated with ribavirin treatment was observed in the viral genomes from the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
176
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 144 publications
(188 citation statements)
references
References 64 publications
12
176
0
Order By: Relevance
“…These authors reported that ribavirin induced a high frequency of genomic mutations that generated viral progeny with reduced infectivity (7,8). A similar effect of high concentrations of ribavirin has been found in cell cultures infected by RNA viruses belonging to several families, including foot-and-mouth disease virus, Hantaan virus, West Nile virus, and GB virus B, a member of the Flaviviridae family that is closely related to HCV (1,9,16,20,44). In addition, ribavirin has been reported to exert an antiviral effect related to errorprone replication in HCV subgenomic replicons, both in Huh7 cell lines and in a full-length binary HCV replication system (5,20,21,48,53).…”
mentioning
confidence: 58%
“…These authors reported that ribavirin induced a high frequency of genomic mutations that generated viral progeny with reduced infectivity (7,8). A similar effect of high concentrations of ribavirin has been found in cell cultures infected by RNA viruses belonging to several families, including foot-and-mouth disease virus, Hantaan virus, West Nile virus, and GB virus B, a member of the Flaviviridae family that is closely related to HCV (1,9,16,20,44). In addition, ribavirin has been reported to exert an antiviral effect related to errorprone replication in HCV subgenomic replicons, both in Huh7 cell lines and in a full-length binary HCV replication system (5,20,21,48,53).…”
mentioning
confidence: 58%
“…The supernatants were extracted with 1,1,2-trichlorotrifluoroethane (Sigma) containing 0.5 M tri-n-octylamine (Sigma), vortexed for 10 s and centrifuged 30 s at 12 000 g. The entire treatment was performed at 0-4 uC, using ice-cold solutions. Nucleotides were separated using a 4.66250 mm Partisil 10 SAX column (Whatman) with a 4.6630 mm Partisil 10 SAX precolumn (Phenomenex), using buffers and elution conditions described by Airaksinen et al (2003). Chromatograms were analysed using the Unicorn 3.00 software (Amersham Pharmacia Biotech).…”
Section: Methodsmentioning
confidence: 99%
“…This unique biochemical activity and the high mutation rate of RNA viruses have stimulated the interest in the use of mutagenic rNTP analogs to induce virus entry into error catastrophe. Among them, ribavirin (1-␤-D-ribofuranosyl-1,2,3-triazole-3-carboxamide) and 5-f luorouracil have been shown to drive different RNA viruses to extinction through enhanced mutagenesis, including foot-and-mouth disease virus (FMDV) (4)(5)(6)(7)(8)(9)(10)(11). Structural studies on replicative complexes of viral RDRPs, template-primers, and rNTP substrates or analogs are needed to understand the molecular basis of the low fidelity of copy of these enzymes and the mutagenic activities displayed by rNTP analogs on viral replication.…”
mentioning
confidence: 99%